An adaptability evaluation of large-scale solar energy for hot water application based on energy-economic-environment consideration: A case study of city-residential buildings in China. (10th May 2021) - Wang, Lizhen; Zheng, Donglin; Cheng, Guang
Abstract: Evaluation of city-residential solar hot water systems (SHWS) in a large-scale area is a complicated topic since many endogenous and exogenous factors would affect the results. This paper presents an adaptability evaluation model for regional SHWS in city-residential buildings through using multiple attribute-decision methods. The evaluation factors, including six variable parameters and eight constant parameters, were selected based on energy-economic-environment consideration. In addition, the provincial databases of the utilization of solar energy resources in China were established and 31 provincial capital cities were investigated. The results are summarized as follows: 1) the five most important factors, with summing weights accounting for 54% in total, are the solar radiation intensity, payback period, solar fraction, installation area, and water supply temperature; 2) compared with the evaluation methods regarding different factors, energy-economic-environment adaptability evaluation method is more reliable, especially when there are huge differences existing in solar energy resources, economic levels, and energy prices. 3) sensitivity analysis shows that it has little influence on the evaluation results when the weight of the first level evaluation index changes within 25%. The conclusions in this paper provide valuable guidance for renewable energy planner and decision makers.